Differential Inhibition of the Platelet Activation Sequence: Shape Change, Micro- and Macro-Aggregation, by a Stable Prostacyclin Analogue (lloprost) - Pedvis, L G; Wong, T; Frojmovic, M M (Thrombosis and Haemostasis, 1988)
The relative sensitivities of adenosine diphosphate (ADP)-induced activation, and of prostaglandin-mediated inhibition, were determined for rates of platelet shape change (SC [Vs]), early platelet recruitment measured by electronic platelet counting (PA [PA3]), and turbidometrically-measured aggregation (TA[Va]). Studies were performed in stirred citrated platelet-richplasma from 9 healthy human donors. The [ADP]1/2, ([ADP]giving half maximal rate) was determined for the sequence of activation steps: unactivated platelets → SC → PA → TA. Distinct ADP sensitivities were obtained from log dose-responsestudies, with a relative dose dependency for rates of change in the order of [ADP]1/2 TA > [ADP]1/2 PA > [ADP]1/2 SC of ~4:3:1.Differential inhibition of the above activation scheme was evalu-ated from log dose-response curves for lloprost (ZK 36374), astable carbacyclin analogue of prostacyclin (PGI2), with greaterpotency than PGI2 for the same platelet receptors. IC50 valuescorresponding to lloprost concentrations causing 50% inhibitionof rates of TA (Va), PA (PA3) and SC (Vs) were found in therelative ratios of 1: ~3: ~5, when measured at a common ADPconcentration for all three parameters, or 1: ~2: ~3 when deter-mined at respective [ADP]1/2 values for each parameter. Thus, about 3-5 times more lloprost is required to respectively inhibitthe rates of shape change (Vs) and early platelet recruitment(PA3), than that needed to inhibit the rate of turbidometrically-measured aggregation (Va).
Keywords: Differential activation and inhibition; Shape change; Microaggregation; Macroaggregation; lloprost (ZK 36374)